THE ROLE OF OXIDATIVE PHOSPHORYLATION IN THE MECHANISM OF HUMAN SPERM MOTILITY REGULATION - Sudjarwo Sudjarwo; Aucky Hinting; Noor Cholies Zaini (The East Java Biological Society, 2006)
Energy synthesis for sperm motility in the mitochondria with enzymatic reactions in nucleus and mitochondria is called Oxidative Phosphorylation (OXPHOS), in which the respiratory process is coordinated in nucleus and mitochondria. Enzymes in OXPHOS process are complex enzymes I, III, IV and V in the mitochondria and complex enzyme II in the nucleus. If there is OXPHOS dysfunction, the mutation of mitochondria DNA (mtDNA) will decrease energy (ATP, Adenosine Triphosphate) production and increase Reactive Oxygen Species (ROS). The characteristics of ROS are oxidant for lipid, protein and DNA, and all these reactions lead to the dysfunction of OXPHOS and, in the spermatozoa, they will decrease motility. The detection of ROS, Malondialdehyde (MDA), 8-hydroxydeoxyguanosine (8-OH-dG), and sperm motility can use Chemiluminicense method, Spectroflourometric method, High Performance Liquid Chromatography (HPLC) method and Markler method, respectively, as World Health Organization (WHO) Procedures Laboratory. These results indicated there was significant indirect correlation between ROS with sperm motility and direct correlation between ROS with MDA, 8-OH-dG.